2019
DOI: 10.1002/ca.23525
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral symmetry of the subtalar joint facets and the relationship between the morphology and osteoarthritic changes

Abstract: There is a paucity in the literature regarding bilateral symmetry between the facets of the subtalar joint. Often surgeons use the contralateral side as a reference when dealing with a fracture or other joint pathology. Moreover, the presence of osteoarthritic (OA) changes in the subtalar joint is suggested to have a relation with its morphology. In this study, we addressed both these issues. Forty pairs of cadaveric tali and calcanei were analyzed by dissection and measurement. Twenty pairs of asymptomatic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…The present study did not find any relationship between joint structure of the subtalar joint (number of articular facets of the talus and calcaneus, joint congruence, or intersecting angle) and degeneration of the subtalar articular facet. These results were similar to those described by Kleipool et al [11], who examined relationships between the number of articular facets, joint congruence, intersecting angle and degeneration of the subtalar articular facet in bone specimens with residual soft tissue. Kleipool et al [11] also considered that the degeneration of the subtalar articular facet observed in bleached bone may reflect secondary features of degeneration, while bone with remaining soft tissue may allow detection of early-stage degeneration of the articular cartilage.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The present study did not find any relationship between joint structure of the subtalar joint (number of articular facets of the talus and calcaneus, joint congruence, or intersecting angle) and degeneration of the subtalar articular facet. These results were similar to those described by Kleipool et al [11], who examined relationships between the number of articular facets, joint congruence, intersecting angle and degeneration of the subtalar articular facet in bone specimens with residual soft tissue. Kleipool et al [11] also considered that the degeneration of the subtalar articular facet observed in bleached bone may reflect secondary features of degeneration, while bone with remaining soft tissue may allow detection of early-stage degeneration of the articular cartilage.…”
Section: Discussionsupporting
confidence: 89%
“…These results were similar to those described by Kleipool et al [11], who examined relationships between the number of articular facets, joint congruence, intersecting angle and degeneration of the subtalar articular facet in bone specimens with residual soft tissue. Kleipool et al [11] also considered that the degeneration of the subtalar articular facet observed in bleached bone may reflect secondary features of degeneration, while bone with remaining soft tissue may allow detection of early-stage degeneration of the articular cartilage. In this study, articular cartilage degeneration and osteophyte formation were analyzed as degeneration of the subtalar articular facet, which may have allowed more comprehensive evaluation than in previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Intersecting angles may therefore also be related to degeneration of the subtalar articular facet [ 8 , 9 ]. However, recent reports on bones with residual soft tissue, including cartilage, found significant associations between morphology of the articular facet, joint congruence, or intersecting angle and degeneration of the subtalar articular facet [ 11 ], and agreement is lacking among previous studies.…”
Section: Introductionmentioning
confidence: 99%